From Job Crafting to Work Engagement: The Moderating Role of Flourishing in Millennial Educational Personnel - Maharani Tyas Budi Hapsari; Nurul Badriyah; Fitri Yusmia Putri (Journal An-Nafs: Kajian Penelitian Psikologi, 2026)
Millennial-generation employee tend to have low work engagement in their organizations. Low work engagement can lead to negative behavior at work. This study aims to examine the role of flourishing as a moderating variable in its effect on job crafting on work engagement among millennial educators. The sample in this study consisted of 95 research subjects. comprising 63 females and 32 females with professions as teachers, lecturers, and educational staff.  The Work Engagement Scale is modified from Schaufeli et al. The Job Crafting Scale used in this study is modified from Tims et al. The Flourishing Scale used in this study refers to Diener et al. 's scale. The Moderation analysis using Hayes' PROCESS Macro indicated that flourishing significantly moderated the relationship between job crafting and work engagement (β = -0.0107, 95% CI [-0.0199, -0.0016], p = .0215). The negative interaction coefficient suggests that the positive effect of job crafting on work engagement decreases at higher levels of flourishing. The model accounted for 67.41% of the variance in work engagement (R² = .6741). This study implies that educational institutions should maintain a balance between enhancing employee flourishing and encouraging proactive work behavior. Educational institutions can support this goal by providing opportunities for teachers, lecturers, and educational staff to participate in curriculum development, lead improvement projects, and implement innovative ideas that contribute to educational quality and service effectiveness.